Thymoquinone subdues tumor growth and potentiates the chemopreventive effect of 5-fluorouracil on the early stages of colorectal carcinogenesis in rats - Kensara OA; El-Shemi AG; Mohamed AM; Refaat B; Idris S; Ahmad J (Dove Medical Press, 2016)
Osama Adnan Kensara,1,* Adel Galal El-Shemi,2,3,* Amr Mohamed Mohamed,2,4 Bassem Refaat,2 Shakir Idris,2 Jawwad Ahmad2 1Department of Clinical Nutrition, Faculty of Applied Medical Sciences, Umm Al-Qura University, Holy Makkah, Saudi Arabia; 2Department of Laboratory Medicine, Faculty of Applied Medical Sciences, Umm Al-Qura University, Holy Makkah, Saudi Arabia; 3Department of Pharmacology, Faculty of Medicine, Assiut University, Assiut, Egypt; 4Department of Animal Medicine, Faculty of Veterinary Medicine, Assiut University, Assiut, Egypt *These authors contributed equally to this work Abstract: Colorectal cancer (CRC) is one of the most prevalent cancers and has a high mortality rate. Insensitivity and the limited therapeutic efficacy of its standard chemotherapeutic drug, 5-fluorouracil (5-FU), represents an important challenge in CRC treatment. The robust antitumor properties of thymoquinone (TQ), the main bioactive constituent of Nigella sativa, have recently been demonstrated on different cancers. We investigated whether TQ could potentiate the chemopreventive effect of 5-FU to eradicate the early stages of CRC and elucidated its underlying mechanisms. An intermediate-term (15 weeks) model of colorectal tumorigenesis was induced in male Wistar rats by azoxymethane (AOM), and the animals were randomly and equally divided into five groups: control, AOM, AOM/5-FU, AOM/TQ, and AOM/5-FU/TQ. TQ (35 mg/kg/d; 3 d/wk) was given during the seventh and 15th weeks post-AOM injection, while 5-FU was given during the ninth and tenth weeks (12 mg/kg/d for 4 days; then 6 mg/kg every other day for another four doses). At week 15, the resected colons were subjected to macroscopic, histopathological, molecular, and immunohistochemical examinations. Interestingly, 5-FU/TQ combination therapy resulted in a more significant reduction on AOM-induced colorectal tumors and large aberrant crypts foci than treatment with the individual drugs. Mechanistically, 5-FU and TQ remarkably cooperated to repress the expression of procancerous Wnt, β-catenin, NF-κB, COX-2, iNOS, VEGF, and TBRAS and upregulate the expression of anti-tumorigenesis DKK-1, CDNK-1A, TGF-β1, TGF-βRII, Smad4, and GPx. Overall, our findings present the first report describing the in vivo enhancement effect of combined TQ and 5-FU against early stages of CRC; however, further studies are required to determine the value of this combination therapy in an advanced long-term model of CRC and also to realize its clinical potential. Keywords: colorectal tumors, thymoquinone, 5-fluorouracil, combination therapy, rats